O acesso geográfico à saúde no triângulo fluvial do setor central da Amazônia - Larissa Cristina Cardoso dos Anjos; Adoréa Rebello da Cunha Albuquerque (Confins)
This paper presents the results of an analysis of the conditions of geographical access to health services in the central sector of the Brazilian Amazon, which corresponds to the Metropolitan Region of Manaus (RMM). The methodological procedures included fieldwork and participant research techniques applied an island complex located in the S / SO sector of the city of Iranduba, called in this study "Fluvial Triangle". During the visits it became possible to identify conditions of extreme difficulty of geographical access, established, especially, in the period of the drought, where islands are transformed into geographical barriers. At this stage, transport and circulation costs increase, as does the distance of travel to reach healthcare services. The location of cities also proved to be a barrier to geographical access to health services, especially in the municipalities of Careiro da Várzea and Manaquiri. Due to the distances of the rural areas located around these municipalities, the conditions of geographical access become more expensive and time-consuming, triggering the migration of the population to the nearest municipality, Iranduba. With reference to the geographical access to healthcare in the Fluvial Triangle of the RMM, the distance factor should be considered as the most important in the planning and territorial health system organization.